Analisis Kebutuhan Sumber Daya Manusia Dan Manajemen Hubungan Industrial Pada Karyawan Administrasi Di RSUD Bandung Kiwari - Resya Dwi Marselina; Adjie Saepul Adha; Azfi Shafia Marwah Anandhita; Depi Febriyan; Siti Maesaroh; Tiara Mustika Saldan (Pusat Riset dan Inovasi Nasional, 2025)
The Human Resources (HR) is a key element in carrying out organizational operational activities. Quality HR can provide the best service to customers. The quality and competence of employees can be influenced by effective industrial relations management. This study aims to analyze the needs of human resources and industrial relations management at RSUD Bandung Kiwari. The research method used is qualitative analysis with a descriptive approach. The results of the study show that the analysis of human resource needs and industrial relations management are interrelated. The analysis of human resource needs aims to determine the quantity, qualifications, and competencies needed by the organization, while industrial relations management aims to create a conducive and harmonious work environment. The administrative human resource needs are measured by workload analysis. Industrial relations management for administrative employees at RSUD Bandung Kiwari is already conducive and harmonious, in accordance with the provisions in the employment agreement.